Anxiety at work : 8 strategies to help teams build resilience, handle uncertainty, and get stuff done - Gostick, Adrian Robert; Elton, Chester; Gostick, Anthony (Harper Business, an imprint of HarperCollinsPublishers, 2021)
"Executive coaches Adrian Gostick and Chester Elton detail eight steps for managers to mitigate work anxiety and for employees to cope with their anxiety"--